ACCESSORY MINERALS IN ARCHEAN KOMATIITES OF THE KURSK MAGNETIC ANOMALY - Plaksenko A.N.; Bocharov V.L.; Lyakhovich V.V.; Ipat'yeva I.S.; Vishnevskiy A.A. (My University, 1988)
Peridotitic komatiites of Late Archean greenstone belts of the Kursk Magnetic Anomaly, first identified by Krestin, are recognizable by their present mineral composition and petrography, as well as by relict textural and structural features, which persisted during metamorphism because of selective replacement of the minerals by secondary association and the resulting formation of pseudomorphs, emphasizing shapes, sizes and distribution patterns of mineral grains. In the komatiite samples studied, 27 accessory minerals were found. In set of species, pattern of distribution and content of accessory minerals, these rocks are comparable to comagmatic ultramafic rocks of the greenstone structures of the Kursk Magnetic Anomaly, a fact indicating that they belong to the same petrographic association. Analysis of the species composition and concentrations of accessory komatiite minerals also reveals certain characteristic features, which the paper describes, along with typomorphic features of the most common accessory komatiite minerals.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей